Understanding Gen Z's Netflix usage in Indonesia: an Extended TAM perspective on willingness to subscribe - Marela, Andea Ndari; Alfansi, Lizar (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
This research constitutes an innovative contribution by exploring Generation Z's inclination to subscribe to Netflix. As this demographic dominates streaming platforms, understanding factors influencing subscription willingness is crucial in the digital entertainment industry. The study analyzes variables such as Perceived Usefulness, Perceived Ease of Use, Content Richness, Interactivity, and Perceived Price from the perspective of Generation Z in Indonesia. Utilizing the Structural Model with Partial Least Squares (PLS), online questionnaires were distributed through social media, garnering 300 responses. Findings reveal that Perceived Price, Perceived Usefulness, and Perceived Ease of Use significantly influence the Willingness to subscribe to Netflix among Generation Z in Indonesia. Interactivity positively impacts Perceived Usefulness, while Content Richness lacks a significant influence. These results underscore the importance for streaming providers like Netflix to ensure perceived value in pricing, prioritize user-friendliness, and leverage interactive features for an enhanced subscription experience. Aligning content with user preferences remains crucial for a nuanced understanding of the content-user relationship within the digital landscape.